(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
ICT and E-Business in the Banking Industry (hereafter the BI) have had a considerable influenceon banks with physical branches. One of the most essential considerations in choosing on e-businesscomponent investments is value generation. Previously 10 years, banks have made significantinvestments to use the Internet and turn their conventional operations into e-businesses. Nationalized andprivate banks have increasingly turned to e-business to take advantage of business efficiency prospects.These banks used the Business to Consumer (B2C) e-business model to expand their market share,improve customer service, and reach out to clients across longer distances.